(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article reflects the importance of organizing clusters of agricultural production and processing in providing employment to the rural population, off ers training based on the public-private partnership, as well as the direction of creating new jobs in clusters of agricultural production and processing.